2022
DOI: 10.1590/0102-672020220002e1675
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Surgical Wound Infection After Elective Laparoscopic Cholecystectomy

Abstract: BACKGROUND: One of the ways to avoid infection after surgical procedures is through antibiotic prophylaxis. This occurs in cholecystectomies with certain risk factors for infection. However, some guidelines suggest the use of antibiotic prophylaxis for all cholecystectomies, although current evidence does not indicate any advantage of this practice in the absence of risk factors. AIMS: This study aims to evaluate the incidence of wound infection after elective laparoscopic cholecystectomies and the use of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
5
0
3
Order By: Relevance
“…Para realizar un procedimiento quirúrgico es necesario determinar si el paciente está en condiciones óptimas para ser interviniendo quirúrgicamente, estos indicadores se mantienen durante todo el proceso peri operatorio con el objetivo de realizar una cirugía segura y evitar complicaciones (Macías,2022), los parámetros que se evalúan son tiempo de ingreso, realización de profilaxis antimicrobianas 24 horas antes o por los menos 30 a 60 minutos antes de la incisión, para maximizar la concentración de antibióticos en los tejidos, realización del procedimiento de antisepsia del campo operatorio y control del nivel de glucemia postoperatoria en los pacientes que tengan diabetes siendo esto un factor de riesgo (Gamo et al, 2022;Guo et al,2022). ISSN en línea: 2789-3855, marzo, 2023, Volumen 4, Número 1, p. 2586.…”
Section: Resultsunclassified
“…Para realizar un procedimiento quirúrgico es necesario determinar si el paciente está en condiciones óptimas para ser interviniendo quirúrgicamente, estos indicadores se mantienen durante todo el proceso peri operatorio con el objetivo de realizar una cirugía segura y evitar complicaciones (Macías,2022), los parámetros que se evalúan son tiempo de ingreso, realización de profilaxis antimicrobianas 24 horas antes o por los menos 30 a 60 minutos antes de la incisión, para maximizar la concentración de antibióticos en los tejidos, realización del procedimiento de antisepsia del campo operatorio y control del nivel de glucemia postoperatoria en los pacientes que tengan diabetes siendo esto un factor de riesgo (Gamo et al, 2022;Guo et al,2022). ISSN en línea: 2789-3855, marzo, 2023, Volumen 4, Número 1, p. 2586.…”
Section: Resultsunclassified
“…This can avoid performing the hepaticojejunostomy in an ischemic portion of the common bile duct, or in a portion with thermal injury or fibrotic tissue, and therefore, prevent the failure of the anastomosis. It has already been demonstrated that on-table repair by non-HPB specialists appears to be an independent risk factor for biliary strictures, recurrent cholangitis, revision surgery, and overall morbidity 9 , 19 . On the other hand, early referral can decrease the incidence of strictures and postoperative complications 27 , as well as the risk of litigation 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Oral antimicrobials are commonly administered alongside bowel preparation, which is a highly debated topic in the literature. Major perioperative care protocols such as Enhanced Recovery After Surgery and Acerto recommend limiting bowel preparation 6 , 19 , 24 , 26 . The rationale behind this is to reduce hydroelectrolytic imbalance and the need for intravenous fluids during the perioperative period 24 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Major perioperative care protocols such as Enhanced Recovery After Surgery and Acerto recommend limiting bowel preparation 6 , 19 , 24 , 26 . The rationale behind this is to reduce hydroelectrolytic imbalance and the need for intravenous fluids during the perioperative period 24 , 26 . The concept of no bowel preparation in elective colorectal surgery is supported by a randomized trial from Finland (MOBILE trial), which showed no difference in terms of SSIs and overall morbidity between mechanical bowel preparation, oral antibiotic bowel preparation, and no bowel preparation 32 .…”
Section: Introductionmentioning
confidence: 99%